New Attorney Swearing In Ceremony at Exhibit Hall - Watkins, Howard::::::::: (1984)
Appellate Court Clerk Kevin Swanson administering the oath to the new attorneys; back side of Swanson and faces of the new attorneys showing Dennis Marshall in front row, third from right end